A Website with Ordering and Inventory System for XYZ Organic Shop - De Guzman, Annie Vironica F; Llave, Earl Joseph Y; Saludo, Nicole Anne; Barut, Bryan B.; Reyes, Victoria M; Villones, Roman B.; Crisostomo, Suzette C. (International Journal of Computing Sciences Research, 2024)
The study's objective is to create an online ordering system for the XYZ Organic Shop. It is to construct and develop an online shop system that will assist Picky Organic Shop and its employees in marketing their business through an e-commerce platform to increase their popularity. The Agile methodology enables the efficient construction of all system development components by prioritizing client requirements and expected system structure. Agile Methodology is utilized by the proponents because it enables them to identify the relevant enhancements and improvements suggested and requested by the client in relation to the functionality and design of the system for Picky Organic Shop. Overall, the XYZ Organic Shop's online ordering system is advantageous for its ability to assist customers in acquiring their desired products in a contemporary setting, as it is convenient and uncomplicated. In addition, it indicates that the system's average score was 4.0 and that it is Acceptable based on the functionality evaluation criteria. Also, it demonstrates how dependent the modern world is, which can help this business gain a foothold in the e-commerce world. Based on the process of evaluation result, the system is effective and efficient. This results in a streamlined purchasing experience for both front-end and back-end users, as customers can quickly obtain their desired items via the front-end website and back-end users can easily monitor item quantities and receive alerts when a product shortage is imminent. In the event that a customer raises a concern, future expansion may include a more refined customer service department as well as additional payment options. The system's capability to verify the authenticity of consumer reviews is also a potential area for development. This process will eventually result in customers receiving their desired products, offers, and services, which will presumably attract more attention to the small business, resulting in a profit increase.